Determinants of Hybrid Investor Behavior: Selecting Stock in The Islamic Capital Market with Maqasid of Sharia as Moderation - Jalari Jalari; Syamsul Anwar; Misnen Ardiansyah (Millah: Journal of Religious Studies, 2023)
The focal point of this research is the hybrid investor behavior and maqaá¹£id of sharia. Understanding maqaá¹£id of sharia is the right solution to negative public perceptions of investment in the Islamic capital market. Hybrid investor behavior comprises two variables: perceived risk and behavioral hybrid, which lead to different results. This study aims to find new theories about the behavior of hybrid investors towards stock options with maqaá¹£id of sharia as a moderating variable to strengthen scientific thinking to conceptually and contextually identify, evaluate, and execute the existing problems in choosing sharia stocks. This was an explanatory research study with a nonexperimental research design. This study used a quantitative method, and data were collected through questionnaires distributed to hybrid investors in Surakarta areas: Surakarta, Boyolali, Klaten, Sukoharjo, Wonogiri, Karanganyar, and Sragen. It involved 130 investors as research participants. The data were analyzed using Structural Equation Modeling to obtain a model that explains the relationship between the variables on Sharia stock options. This research revealed that the perception of risk has a negative and significant effect on the choice of Islamic stocks. Hybrid behavior has a positive and significant effect on the choice of Islamic stocks. Maqaá¹£id sharia moderates the effect of risk perception on sharia stock options and does not moderate the effect of hybrid behavior on the choice of sharia stocks.